(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Destination communication is essential for improving the economic and social development of cities, regions and countries, as tourism has become a major component of gross domestic product in most countries of the world. The development of information technology has fundamentally changed the use of traditional communication tools. Due to the development of modern information technologies, the Internet has become an integral part of tourism communication. Aim of the research is to explore the use of digital marketing in tourism promotion in Latgale region. Research methods - document analysis, statistical data analysis, survey - surveyed tourism information providers in Latgale region; statistical grouping, reading method, interview. The results of the research show that only 20% of Latgale region tourism information providers are actively involved in the use of social media. In the work of tourism information providers more attention is paid to printed materials than to video materials in the digital environment. But the most effective means of digital marketing is that all tourism information providers emphasize the importance of social networks. Digital Marketing Costs has only 40% of the Latgale region tourism information providers and they make between 100 and 3000 euros per year. On Visitlatgale.com and latgale.travel, most of the analyzed digital marketing criteria are not present. Latgale marketing action plan is quite varied and wide where costs are for many exhibitions both in Latvia and abroad, visits of Latvian tour operators and journalists, visits of foreign tour operators and bloggers, training seminars, but the marketing plan for 2019 does not include expenses for digital marketing. Latgale Region Tourism Association Ezerzeme marketing plan necessary to provide expenditure for the development of a communication plan - actively should be used funded projects possibilities, for example costs can be partly covered by the European Union's European Agricultural Fund for Rural Development (EAFRD) and the Rural Development Program. Latgale Region Tourism Association needs to attract project funding for tourism information providers training in digital marketing. More attention should be paid to publishing video materials and attracting appropriate specialists. Latgale Planning Region and Rezekne Municipality should improve tourism websites Latgale.travel and visitlatgale.com.